A Tri-part Protein Complementation System Using Antibody-Small Peptide Fusions Enables Homogeneous Immunoassays - Andrew S. Dixon (Nature Portfolio, 2017)
Abstract Protein-fragment complementation is a valuable tool for monitoring protein interactions. In complementation assays, the reporter fragments are directly fused to the interacting proteins, eliminating the possibility of monitoring native interactions. In principle, complementation could be achieved by placing the reporter fragments on antibodies which bind to the proteins of interest, enabling the monitoring of endogenous protein interactions or detection of a single protein in a homogeneous immunoassay. Previous reports have demonstrated proof-of-concept of this approach; however, current complementation systems have not met the practical requirements as suitable fusion partners for antibodies while providing the sensitivity needed for immunoassays. To surmount these challenges, we created a first-in-class, tri-part split luciferase consisting of two 11-residue peptides that are used as the antibody appendages. As an initial proof-of-concept, we used antibody-peptide fusions and found them to be capable of quantifying pg/mL concentrations of soluble or cell-bound HER2, proving this unique complementation system overcomes previous limitations and transforms this approach from merely possible to practical and useful. As shown herein, this dual-peptide system provides a rapid, simple, and sensitive “add-and-read” homogeneous immunoassay platform that can be broadly adapted as an alternative to traditional immunoassays, and in the future should enable complementation to be expanded to monitoring endogenous protein interactions.